Reliability of India-specific regression formula for age estimation of population in and around Bahadurgarh, Haryana (India) - Ankita Tandon; Vartika Agarwal; Varun Arora (Journal of Oral Biology and Craniofacial Research)
Objectives: The study was conducted to check the reliability of India-specific regression formula for age estimation of population in and around Bahadurgarh, Haryana (India). Materials and methods: The study was conducted using digital orthopantomograms (OPGs) of 464 subjects (253 males and 211 females). Chronologic age (CA) was derived from that mentioned on the OPG. Each tooth in the left mandibular segment was scored using Demirjian's scoring and age was calculated using the regression formulas derived by Acharya. The difference of the chronologic and estimated age was used to check the reliability of India-specific regression formula. Results: The mean estimated age was found to be significantly higher as compared to CA for overall as well as both the genders independently (p < 0.001). Difference (in ±) between estimated and CA ranged from 0 to 4.2 years. Mean difference in age was 0.85 ± 0.73 years for males and 0.87 ± 0.76 years for females. Conclusion: The published India-specific regression formula does not have reliability in the population of Bahadurgarh, Haryana and hence cannot be universally applied.